2008
DOI: 10.1002/cyto.a.20683
|View full text |Cite
|
Sign up to set email alerts
|

Studies related to antibody fragment (Fab) production in Escherichia coli W3110 fed‐batch fermentation processes using multiparameter flow cytometry

Abstract: Microbiology is important to industry therefore rapid and statistically representative measurements of cell physiological state, proliferation, and viability are essential if informed decisions about fermentation bioprocess optimization or control are to be made, because process performance will depend largely on the number of metabolically active viable cells. Samples of recombinant Escherichia coli W3110, containing the gene for the D1.3 anti-lysozyme Fab fragment under the control of the lac-based expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…This indicates that the use of the same disruption intensity can be used to measure cell strength which declines as the culture is subjected to longer bioreactor operation. This is in accordance with Want et al 31 who noted a progressive and detrimental change in cell physiological state (also using E. coli W3110) with respect to permeability using flow cytometry. From a processing perspective, this leads to weaker host cell outer membranes that have the potential to damage on entering the high shear zones of industrial centrifuges during the subsequent solid-liquid separation.…”
Section: Cell Integrity-intracellular Rate Of Product Releasesupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that the use of the same disruption intensity can be used to measure cell strength which declines as the culture is subjected to longer bioreactor operation. This is in accordance with Want et al 31 who noted a progressive and detrimental change in cell physiological state (also using E. coli W3110) with respect to permeability using flow cytometry. From a processing perspective, this leads to weaker host cell outer membranes that have the potential to damage on entering the high shear zones of industrial centrifuges during the subsequent solid-liquid separation.…”
Section: Cell Integrity-intracellular Rate Of Product Releasesupporting
confidence: 90%
“…35 Also, the increase in the amount of product in the periplasmic space with culture age may apply pressure on the outer cell membrane resulting in outer membrane weakening. 31 Micronization susceptibility has important implications for unit operations further downstream both at a technical and economic level. Smaller cell debris that cannot be efficiently well separated during solid-liquid separation will create unacceptable fouling of clarifying filters that would need to be of a bigger size (larger filtration area) to avoid a decrease in clarifying efficiency.…”
Section: Shear Sensitivitymentioning
confidence: 99%
“…Sundstöm et al [60] studied the effects of inclusion body formation on cell physiology during the production of promegapoietin by E. coli. Similar observations were made using the same microbial chassis but with another recombinant protein (Fab antibody fragment) leading to the formation of inclusion bodies [63]. In related studies, it was demonstrated that the microbial chassis influences the heterogeneity of recombinant protein production.…”
Section: Production Of Metabolites and Recombinant Systems: Robustnesmentioning
confidence: 67%
“…In both cases within 4 h of inoculation almost all cells were either only Chamsartra et al, 2005;Amanullah et al, 2002) and the dual staining combination with PI/bisoxanol is suitable for Gram -ve cells e.g. E. coli, Salmonella spp., Acinetobacter johnsonii (Boswell et al, 1998;Want et al, 2009.;Hewitt & Nebe-von-Caron 2001;Nebe-von-Caron et al, 2000;Boswell et al, 1998). This is likely to be species and process specific whilst the interpretation of such data can only be reliably …”
Section: Resultsmentioning
confidence: 99%